The Impact of Vlogging on EFL Learner’s Fluency and Self-Confidence in the Classroom - Zulfa Salshabila Prastowo (Arden Jaya Publisher, 2026)
Speaking is one of the most important skills in English language learning; however, many English as a Foreign Language (EFL) learners in Indonesia experience difficulties in speaking fluently and confidently due to limited exposure to English, insufficient opportunities for practice, and high levels of speaking anxiety. To address these challenges, this study investigated the impact of vlogging on students’ speaking fluency and self-confidence in an EFL classroom. The study employed a quantitative quasi-experimental design with pre-test and post-test measures involving eleventh-grade students at a vocational high school in Sidoarjo, East Java, Indonesia. The participants were divided into an experimental group, which engaged in vlogging activities, and a control group, which received regular speaking instruction. Data were collected through a speaking test to assess students’ fluency and a Likert-scale questionnaire to measure their self-confidence. The collected data were analyzed using descriptive statistics and Analysis of Covariance (ANCOVA). The findings revealed that, after controlling for pre-test scores, the implementation of vlogging did not produce a statistically significant effect on students’ speaking fluency. Nevertheless, students in the experimental group demonstrated improvement in their speaking performance and benefited from opportunities for repeated practice and self-reflection. In contrast, the results showed a statistically significant improvement in students’ self-confidence, indicating that vlogging helped learners become more comfortable and confident in using English. These findings suggest that vlogging can serve as an effective instructional strategy for enhancing learners’ self-confidence and promoting active participation in speaking activities. However, longer implementation periods and additional instructional support.